PERBANDINGAN EFEKTIFITAS METODE ANTRIAN PADA SAAT COVID-19 DAN SEBELUM COVID-19 (Studi Kasus: BNI UNSRAT Manado) - Rio Ohoirat (Universitas Sam Ratulangi, 2023)
On January 11, 2022, the number of COVID-19 cases in Indonesia had reached 4,267,451 of which 34,724 were confirmed to be in North Sulawesi. One of the sectors that was affected was the banking sector due to the declining demand for work loans. In every area, the bank is a safe place to save money. one of the banks in North Sulawesi, namely BNI 46 UNSRAT Manado Branch, in order to suppress the spread of COVID-19, the queuing system is an important element in helping to suppress the spread in public places. The purpose of this study was to find out how to compare the effectiveness of the performance of the BNI 46 queuing system model at the UNSRAT Manado branch during COVID-19 and before COVID-19. This study uses a qualitative descriptive approach, namely direct observation techniques on the performance of the teller queuing system. The results of this study indicate that there are differences in the level of effectiveness of the performance of the queuing system model during COVID-19 72.80 and before COVID-19 156.13 thus the performance of the queuing method is reduced and on the teller's side there is a reduction in performance productivity.